ELASTICITY OF CASNO3 PEROVSKITE - Kung J.; Angel R.J.; Ross N.L. (My University, 2001)
The elastic properties of CaSnO3 perovskite have been measured by both ultrasonic interferometry and single-crystal X-ray diffraction at high pressures. The single-crystal diffraction data collected using a diamond-anvil cell show that CaSnO3 perovskite does not undergo any phase transitions at pressures below 8.5 GPa at room temperature. Ultrasonic measurements in the multianvil press to a maximum pressure of ~8 GPa at room temperature yielded S- and P-wave velocity data as a function of pressure. For a third-order Birch-Murnaghan EoS the adiabatic elastic moduli and their pressure derivatives determined from these velocity data are K S0=167.2±3.1 GPa, K ′ S0=4.89±0.17, G 0=89.3±1.0 GPa, G ′ 0=0.90±0.02. The quoted uncertainties include contributions from uncertainties in both the room pressure length and density of the specimen, as well as uncertainties in the pressure calibration of the multianvil press. Because the sample is a polycrystalline specimen, this value of KS0 presents an upper limit to the Reuss bound (conditions of uniform stress) on the elastic modulus of CaSnO3 perovskite. If the value of αγT is assumed to be 0.01, the value of KS0 corresponds to KT05.5±3.1 GPa. The 10 P-V data obtained by single-crystal diffraction were fit with a third-order Birch-Murnaghan equation-of-state to obtain the parameters V 0=246.059±0.013 Å3, K T0=162.6±1.0 GPa, K ′ T0=5.6±0.3. Because single-crystal measurements under hydrostatic conditions are made under conditions of uniform stress, they yield bulk moduli equivalent to the Reuss bound on a polycrystalline specimen. The results from the X-ray and ultrasonic experiments are therefore consistent. The bulk modulus of CaSnO3 perovskite lies above the linear trend of K0 with inverse molar volume, previously determined for Ca perovskites. This prevents an estimation of the bulk modulus of CaSiO3 perovskite by extrapolation. However, our value of G0r CaSnO3 perovskite combined with values for CaTiO3 and CaGeO3 forms a linear trend of G0 with octahedral tilt angle. This allows a lower bound of 150 GPa to be placed on the shear modulus of CaSiO3 extrapolation.
Keywords: PEROVSKITE; ELASTICITY; ULTRASONIC MEASUREMENT; X-RAY DIFFRACTION; HIGH PRESSURE